Phenological Asynchrony Is Associated With Diapause Program and Heat Shock Protein Expression in Three Grasshopper Species in the Inner Mongolian Steppe - Chen, Bing; Jiang, Chunyan; Guo, Siyuan; Guo, Kun; Hao, Shuguang (Frontiers in Ecology and Evolution, 2021)
Phenological asynchrony is a common and important natural phenomenon that affects interspecific interaction, resource allocation, species survival, and range shift in sympatric species. However, the underpinnings for regulating phenological asynchrony at physiological and molecular levels remains less explored. We investigated the seasonal pattern of emergence period and abundance in three dominant grasshopper species, namely, Dasyhipus barbipes, Oedalus asiaticus, and Chorthippus dubius, which occur sympatrically in the Inner Mongolian steppe. The three grasshopper species decoupled their population occurrence phenology that occurred in a growing season between May and September and diverged into early, middle, and late seasonal species. We also examined the association of embryonic diapause and heat shock protein (Hsp) expression with phenological asynchrony in the three species. The species developed different embryonic diapause programs, i.e., obligate diapause, facultative diapause, and non-diapause, to control the timing of egg hatching and seasonality of population occurrence. The diapausing eggs exhibited significantly enhanced supercooling capacity compared with pre- and post-diapausing eggs. Gene expression analysis in the developmental process revealed that three Hsps, e.g., Hsp20.6, Hsp40, and Hsp90, were significantly upregulated in diapause state relative to that in pre- and post-diapause states; expression of these genes seems to be associated with the diapause program regulation. This study provides a possible mechanistic explanation for phenological differentiation among sympatric species in a typical steppe habitat and establishes a potential linkage among phenological asynchrony, diapause, and Hsp gene expression. The findings will facilitate our prediction of population dynamics and pest management.